Use a Hold Study to Assess Distribution System Influent Water Quality. Issue 5 (6th May 2019) - Alexander, Matthew T.; Dugan, Alison G.; Wahman, David G.
Abstract : Whether water is coming directly from a drinking water treatment plant or through a metered connection to a consecutive system, water utilities can improve water quality by assessing the stability of the distribution system's influent disinfectant residual and the corresponding potential for disinfection byproduct formation.